2019
DOI: 10.1253/circj.cj-18-1152
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Geometry as a Predictor of In-Stent Neointimal Hyperplasia ― A Computational Fluid Dynamics Study ―

Abstract: Background: Carotid angioplasty and stenting (CAS) is emerging as an alternative treatment for carotid stenosis, but neointimal hyperplasia (NIH) remains a drawback of this treatment strategy. This study aimed to evaluate the effect of variations of carotid bifurcation geometry on local hemodynamics and NIH. Methods and Results: Hemodynamic and geometric effects on NIH were compared between 2 groups, by performing computational fluid dynamics (CFD) simulations both on synthetic models and patient-specific mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…From the hemodynamic point of view, the increased tortuosity might induce disturbances of local hemodynamic environment characterized by low wall shear stress that have been demonstrated to associate with the initiation and progression of atherosclerosis [44][45][46]. For coronary [23,47,48] and carotid stents [11,21,24,42,49], geometry of the blood vessels, especially tortuosity, had been suggested to attribute to not only atherogenesis but also instent NIH [1]. The current study showed an ISR rate of 17.95% in severe ICAS patients and also revealed the important role of vessel tortuosity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the hemodynamic point of view, the increased tortuosity might induce disturbances of local hemodynamic environment characterized by low wall shear stress that have been demonstrated to associate with the initiation and progression of atherosclerosis [44][45][46]. For coronary [23,47,48] and carotid stents [11,21,24,42,49], geometry of the blood vessels, especially tortuosity, had been suggested to attribute to not only atherogenesis but also instent NIH [1]. The current study showed an ISR rate of 17.95% in severe ICAS patients and also revealed the important role of vessel tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…Stent implantation induced vessel straightening, significantly decreased vessel curvature, remodeled the vessel, and changed hemodynamic patterns [ 10 , 29 ]. In coronary and carotid atherosclerosis, stenting showed its ability to change the vessel geometry and the local hemodynamics [ 23 , 24 , 30 ]. In intracranial arteries, previous studies have described the effect of stent-induced straightening of vessels [ 31 ] and vascular angel remodeling [ 32 34 ] during stent-assisted coiling of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the CFD simulation was performed as a steady flow and WSS was used as a hemodynamic parameter, but there are studies reporting that neointimal hyperplasia is not associated with WSS 34 or is associated with oscillatory shear index. 35,36 However, in a systematic review, 37 nine of eleven reports visually comparing maps of hemodynamic parameters and hyperplasia supported the low WSS (steady flow) theory, suggesting that CFD simulation was appropriate. Lastly, any effects on the side branch geometrically changed by straightening the mother artery with stenting in bifurcations were not investigated in this study.…”
Section: Study Limitationsmentioning
confidence: 99%